Becoming young men in a new India : masculinities, gender relations and violence in the postcolony - Philip, Shannon, 1988- (Cambridge University Press, 2022)
Becoming Young Men in a New India tells the gendered story of a changing India through the lives of its young middle class men. Through time spent ethnographically 'hanging-out' with young men in gyms, bars, clubs, trains and gay cruising grounds in India, this book critically reveals Indian men's violence towards women in various city spaces and also shows the many classed and masculine entitlements and challenges that they experience. The book lays bare the often secretive and hidden social worlds of young Indian men and critically analyses the impact young men's actions and identities have not just for themselves, but for the many women they encounter. In this way, it puts forward a critical queer-feminist perspective of men and masculinities in postcolonial India where the politics of class, gender, sexuality, violence and urban spaces come together.